L’usure iconique. Circulation et valeur des images dans le cinéma américain contemporain - Mathias Kusnierz (Transatlantica)
Postmodern Hollywood cinema has been characterized as a highly reflexive art, in which images refer to other images or to themselves—not to the world. As a result, theorists often come to the conclusion that Hollywood cinema no longer speaks about the real. This article counters this assumption by examining the various ways in which images do act upon the real. Relying on Jonathan Beller’s “attention theory of value” and Peter Szendy’s concept of “iconomy,” this article proposes that reflexivity does impact the real, particularly through what we call iconomic energy. Iconomic energy circulates images with usury and thereby increases their ideological value. Once reflexivity has been recognized as a multiple and indirect way of impacting the real, Hollywood cinema emerges as an ideological instrument as much as a tool for emancipation.